2022
DOI: 10.21303/2504-5571.2022.002303
|View full text |Cite
|
Sign up to set email alerts
|

The contemporary challenges municipalities face in effectively implementing municipal service partnerships

Abstract: In South Africa, Municipal Service Partnerships (MSPs) have been in existence afore the global breakout of COVID-19 Pandemic as an essential mechanism to expand and accelerate municipal service delivery in the local government sphere. However, once the National Lockdown (NL) was put in place by the state president Cyril Ramaphosa on the 26 of March 2020, many South African municipalities were and still are pushed to look for assistance from their partners in the private sector in order to help with addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The researchers adopted this design because conceptual papers ultimately create new knowledge by building on carefully selected sources of information combined according to a set of norms. In the case of conceptual papers, arguments are not derived from data in the traditional sense but involve the assimilation and combination of evidence in the form of previously developed concepts and theories (Hirschheim, 2008;Mamokhere, Mabeba & Kgobe, 2022). In that sense, conceptual papers are not without empirical insights but rather build on theories and concepts that are developed and tested through empirical research.…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…The researchers adopted this design because conceptual papers ultimately create new knowledge by building on carefully selected sources of information combined according to a set of norms. In the case of conceptual papers, arguments are not derived from data in the traditional sense but involve the assimilation and combination of evidence in the form of previously developed concepts and theories (Hirschheim, 2008;Mamokhere, Mabeba & Kgobe, 2022). In that sense, conceptual papers are not without empirical insights but rather build on theories and concepts that are developed and tested through empirical research.…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…Jaakkola (2020) The researcher adopted this design because conceptual papers ultimately create new knowledge by building on carefully selected sources of information combined according to a set of norms. In the case of conceptual papers, arguments are not derived from data in the traditional sense but involve the assimilation and combination of evidence in the form of previously developed concepts and theories (Hirschheim, 2008;Mamokhere, Mabeba & Kgobe, 2022). In that sense, conceptual papers are not without empirical insights but rather build on theories and concepts that are developed and tested through empirical research.…”
Section: Research and Methodologymentioning
confidence: 99%
“…Phakeng (2022), indicates that collaboration has been affected and further promotes the idea that countries across the globe and municipalities should work together to overcome dire pandemics such as climate change, poverty, and lack of access to clean drinking water. The importance and challenges of collaboration were also noted in the study by Mamokhere, Mabeba & Kgobe (2022), who attempted to comprehend "the contemporary challenges municipalities face in effectively implementing municipal service partnerships". In their arguments, it was found that when the "national lockdown" was put in place by the state president, Cyril Ramaphosa, on the 26th of March 2020, many South African municipalities were and still are pushed to look for assistance from their partners in the private sector to help with addressing the challenges, imposed by the pandemic, especially, service delivery backlogs.…”
Section: Covid-19 Pandemic Effect On Access To Clean Water and Sanita...mentioning
confidence: 98%
See 1 more Smart Citation
“…The importance and the challenges of collaboration were also noted in the article by Mamokhere, Mabeba & Kgobe (2022), who attempted to comprehend the contemporary challenges municipalities face in effectively implementing municipal service partnerships". In their arguments, it was found that when the national lockdown was put in place by the state president Cyril Ramaphosa on the 26th of March 2020, many South African municipalities were and still are pushed to look for assistance from their partners in the private sector to help with addressing the challenges, imposed by the pandemic, especially, service delivery backlogs.…”
Section: Challenges Of Good Governance In Realizing Sdgmentioning
confidence: 99%